PENGEMBANGAN MODUL INTERAKTIF SEBAGAI PANDUAN PENGGUNAAN ARTICULATE STORYLINE - Dzaky Mubarok; Niko sudibjo (Akademika, 2022)
This study aims to evaluate a product that is developed in the form of an interactive module for employees of the Biro Pengembangan Pembelajaran Multimedia Nusantara University. This development follows the systematic procedure of S. Thiagarajan's 4D development model. This development model consists of four major steps, Define, Design, Develop, Disseminate. The subjects of this study were 21 employees at the Biro Pengembangan Pembelajaran Multimedia Nusantara University. The evaluation of this interactive module includes a feasibility test from experts including, learning design experts, material experts, media experts, and users. The results of this study showed that the trial of learning experts, media experts and material experts stated that this interactive module was feasible to use. The results of the one-on-one got an average score of 3.87, the results of the small group trial with an average value of 3.66, the results of the evaluation test trial showed an average score increase of 34 points with an N-Gain Score of 73%, based on these three trials it was stated that users responded positively and indicated that this interactive module have a good quality and effective in use as a Articulate Storyline Guidance at the Biro Pengembangan Pembelajaran Multimedia Nusantara University.